The Development of Paper Doll Media to Enhance the Fiction Storytelling Creativity of Fourth-Grade Students at SD/MI - Purba, Tiara Paramita Br; Devianty , Rina (Journal of Educational Sciences, 2025)
Storytelling skills play an important role in developing students’ language, imagination, and creativity. However, classroom observations in Grade IV of SDN 106844 Pulau Gambar revealed that students had low motivation in storytelling activities due to the limited variation of media used. This study aims to develop a Paper Doll learning medium as an innovative tool to enhance students’ creativity in fictional storytelling. The research employed the Research and Development (R&D) method with the ADDIE model, involving 19 fourth-grade students and one classroom teacher. The product was validated by experts in content, language, and design, and was categorized as “very feasible.” Field trials indicated highly positive responses from both teachers (100%) and students (98%). Students’ learning outcomes also showed significant improvement, with the average pretest score of 12.63 increasing to 73.68 in the posttest. The N-Gain value of 0.70 indicated a high level of effectiveness, and the paired t-test confirmed a significant difference (p < 0.05) before and after the use of the medium. These findings demonstrate that Paper Doll is a feasible, practical, and effective learning medium for Indonesian language instruction, particularly in improving elementary students’ creativity in fictional storytelling.